Pemberian Aromaterapi Eucalyptus terhadap Tingkat Nyeri Kepala Pasien Hipertensi - Siti Nur’ain Mohamad; Nanang Roswita Paramata; Indra Indra (Journal of Telenursing (JOTING), 2026)
This study aimed to analyze the effect of eucalyptus aromatherapy on headache intensity in patients with hypertension in the working area of Puskesmas Dumbayabulan. The method used was a quasi-experimental study with a non-equivalent control group design. The results of this study showed that there was a significant difference in the reduction of headache intensity between the intervention group that received eucalyptus aromatherapy and the control group that did not receive the intervention, with a p-value of 0.001 (p < 0.05). In conclusion, eucalyptus aromatherapy has an effect on reducing headache intensity in patients with hypertension and can be considered as a non-pharmacological therapy to help reduce headaches in hypertensive patients.   Keywords: Eucalyptus Aromatherapy, Headache Intensity, Hypertension